Benarkah Gender Mempengaruhi Hasil Belajar Bahasa Arab - Wa Muna; Suparno Suparno (STIKes Ibnu Sina Ajibarang, 2024)
His study aims to prove whether there is an effect of gender on Arabic learning outcomes at the elementary school level. The research used a quantitative approach, with the research subjects being students in grades II and IV of Asy-Syafi'i Integrated Islamic Elementary School (SDIT) in the academic year 2023-2024, with a total sample size of 54 students. The data were analyzed using an independent sample t-test. The results of the analysis show that there is no significant difference in Arabic learning outcomes based on gender.